1996
DOI: 10.1017/s0026318400033952
|View full text |Cite
|
Sign up to set email alerts
|

Imagined Cyber Communities, Iranians and the Internet

Abstract: The post information age will remove the limitations of geography.—Nicholas Negroponte, Being DigitalThe internet has been a continually changing forum for communicating that has been taken up by diaspora communities to maintain connections with their countrymates all over the world. In that capacity, the technology has been an easy and innovative avenue for cultural expression. Iranians, for instance, have established on-line magazines, newsgroups, media and business directories, human rights organizations, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The theoretical context here is the notion that prolonged exile does not diminish but may or actually does increase van den Bos Hyperlinked Dutch-Iranian Cyberspace 'interest or involvement in home country politics' (Guarnizo et al [2002: 29] for American cases; Østergaard-Nielsen [2003: 1-2] for German cases). This, together with the fact that most Iranians in the Netherlands have come as political refugees (Verkuyten and Nekuee, 1999: 287), and that Iranian diasporic and transnational cyberspace at large is often political (see Nazeri, 1996;Spellman, 2004a: 959), would lead one to presuppose a dominant political presence in Dutch-Iranian cyberspace: a great many sites, displaying great variety as to content, that are well interconnected as well as closely related to other Dutch-Iranian sites.…”
Section: Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical context here is the notion that prolonged exile does not diminish but may or actually does increase van den Bos Hyperlinked Dutch-Iranian Cyberspace 'interest or involvement in home country politics' (Guarnizo et al [2002: 29] for American cases; Østergaard-Nielsen [2003: 1-2] for German cases). This, together with the fact that most Iranians in the Netherlands have come as political refugees (Verkuyten and Nekuee, 1999: 287), and that Iranian diasporic and transnational cyberspace at large is often political (see Nazeri, 1996;Spellman, 2004a: 959), would lead one to presuppose a dominant political presence in Dutch-Iranian cyberspace: a great many sites, displaying great variety as to content, that are well interconnected as well as closely related to other Dutch-Iranian sites.…”
Section: Ismentioning
confidence: 99%
“…For reasons such as these, usages of Internet technology in Iran are widely perceived as exceptional in the Middle East context (Rahimi, 2003: 102, 110). Internet practices among Iranian diaspora communities, however, remain largely unexplored; although Nazeri (1996) and Graham and Khosravi (2002) are major exceptions. This is despite indications that Internet technologies provide a crucial communication forum for the (transnational) Iranian diaspora (Spellman, 2004a: 947).…”
Section: Introductionmentioning
confidence: 99%
“…Østergaard‐Nielsen 2003: 1‐2 for German cases). This, combined with the facts that most Dutch‐Iranians came to the Netherlands as political refugees (Verkuyten & Nekuee 1999: 287), and that Iranian webspace at large is often political (see Nazeri 1996; Spellman 2004 a : 959; 2004 b : 46), led to the presupposition of a dominant political presence in Dutch‐Iranian cyberspace manifesting itself in a great many sites displaying substantial variety as to content which were well interconnected and closely related to other Dutch‐Iranian sites.…”
Section: National Networkmentioning
confidence: 99%
“…Kivisto 2001: 554‐5; van Amersfoort 2001: 5, 51). Among these communication means, one may include the Internet, which has ‘been taken up by [Iranian] diaspora communities to maintain connections with ... countrymates all over the world’ (Nazeri 1996). Spellman, writing of Iranian communities in London, observed that ‘Internet‐based news groups and chat rooms have ... become an important forum for communication between Iranians living in [Iran] and between Iran and the Iranian Diaspora’ (2004 a : 947; cf.…”
Section: Transnational Patterns14mentioning
confidence: 99%
See 1 more Smart Citation